1998
DOI: 10.1006/bulm.1997.0008
|View full text |Cite
|
Sign up to set email alerts
|

The Minimal Speed of Traveling Fronts for a Diffusive Lotka–Volterra Competition Model

Abstract: This paper concerns the minimal speed of traveling wave fronts for a two-species diffusion-competition model of the Lotka-Volterra type. An earlier paper used this model to discuss the speed of invasion of the gray squirrel by estimating the model parameters from field data, and predicted its speed by the use of a heuristic analytical argument. We discuss the conditions which assure the validity of their argument and show numerically the existence of the realistic range of parameter values for which their heur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(87 citation statements)
references
References 13 publications
1
84
0
Order By: Relevance
“…Unfortunately, this reasoning is, in general, not correct. Hosono (1998) demonstrated that high dispersal of the resident may increase the invader's spread rate above what the linearization predicts. Lewis et al (2002) gave sufficient conditions for the spread rate of an invader to be determined by the single equation obtained from linearizing at the resident-only steady state (linear determinacy).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Unfortunately, this reasoning is, in general, not correct. Hosono (1998) demonstrated that high dispersal of the resident may increase the invader's spread rate above what the linearization predicts. Lewis et al (2002) gave sufficient conditions for the spread rate of an invader to be determined by the single equation obtained from linearizing at the resident-only steady state (linear determinacy).…”
Section: Introductionmentioning
confidence: 94%
“…When the scale of dispersal of the resident species is much larger than that of the invading species, the spread rate of the invading species is not linearly determined in homogeneous habitats (Hosono, 1998;Lewis et al, 2002). The invading species may spread faster than the linearization predicts (see in particular Fig.…”
Section: Failure Of Linear Determinacymentioning
confidence: 99%
“…These match very closely with speeds calculated from the simulation speeds. Even though the minimum possible speed is often the one selected in multispecies waves [see for example, Murray (1989)], it should be noted that this is not always the case (Hosono, 1998). For further discussion of this see Lewis et al (2000) and Weinberger et al (2000).…”
Section: Linear Analysismentioning
confidence: 99%
“…Such waves were rst studied numerically, with analytical solution in a special case, by Okubo et al (1989). Existence of waves was proved by Kan-on (1997), with extension to the case of di¬erent di¬usion coe¯cients considered by Hosono (1998). The work presented in the present paper raises many challenges for the extension of these various results to the new movement term re®ecting contact inhibition.…”
Section: Discussionmentioning
confidence: 87%